Dysbiotic gut microbiota causes transmissible Crohn's disease-like ileitis independent of failure in antimicrobial defence. Issue 2 (17th April 2015) - Schaubeck, Monika; Clavel, Thomas; Calasan, Jelena; Lagkouvardos, Ilias; Haange, Sven Bastiaan; Jehmlich, Nico; Basic, Marijana; Dupont, Aline; Hornef, Mathias; Bergen, Martin von; Bleich, André; Haller, Dirk
Abstract : Objectives: Dysbiosis of the intestinal microbiota is associated with Crohn's disease (CD). Functional evidence for a causal role of bacteria in the development of chronic small intestinal inflammation is lacking. Similar to human pathology, TNF deltaARE mice develop a tumour necrosis factor (TNF)-driven CD-like transmural inflammation with predominant ileal involvement. Design: Heterozygous TNF deltaARE mice and wildtype (WT) littermates were housed under conventional (CONV), specific pathogen-free (SPF) and germ-free (GF) conditions. Microbial communities were analysed by high-throughput 16S ribosomal RNA gene sequencing. Metaproteomes were measured using LC-MS. Temporal and spatial resolution of disease development was followed after antibiotic treatment and transfer of microbial communities into GF mice. Granulocyte infiltration and Paneth cell function was assessed by immunofluorescence and gene expression analysis. Results: GF-TNF deltaARE mice were free of inflammation in the gut and antibiotic treatment of CONV-TNF deltaARE mice attenuated ileitis but not colitis, demonstrating that disease severity and location are microbiota-dependent. SPF-TNF deltaARE mice developed distinct ileitis-phenotypes associated with gradual loss of antimicrobial defence. 16S analysis and metaproteomics revealed specific compositional and functional alterations of bacterial communities in inflamed mice. Transplantation of disease-associated but not healthy microbiota transmitted CD-like ileitis to GF-TNF deltaARE recipients and triggered loss of lysozyme and cryptdin-2 expression. Monoassociation of GF-TNF deltaARE mice with the human CD-related Escherichia coli LF82 did not induce ileitis. Conclusions: We provide clear experimental evidence for the causal role of gut bacterial dysbiosis in the development of chronic ileal inflammation with subsequent failure of Paneth cell function.